EL FENÓMENO DE LOS MOVIMIENTOS GUERRILLEROS EN HONDURAS. EL CASO DEL MOVIMIENTO POPULAR DE LIBERACIÒN CINCHONERO (1980-1990) - Canizales Viril, Rolando (2008)
The following article briefly surveys the political and social history of Honduras in the XX century in an effort to explain the emergence of revolutionary guerilla movements at the end of the 1970s and the beginning of the 1980s, emphasizing the Popular Liberation “Cinchonero” Movement (MPL-C).  It discusses the difficulties that this political group confronted in the face of reformism of the Honduran political culture and the particularities of rural society.  Furthermore, it gives evidence of how the exclusive character of the 1980-1981 elections that marked the transition to civilian governments, reduced their efficiency as a possible factor of social balance.  Also noteworthy is the influence that social movements in neighboring countries practiced, above all in El Salvador, in the conformation of the MPL-C.